27 Percutaneous endoscopic gastrostomy tubes; a retrospective analysis in patients with head and neck cancer over 5 years. (5th April 2017) - Auliffe, E Mc; Murphy, C; Clifford, E; Perrott, L; Heavers, A; O'Hanlon, D
Abstract : Background: Weight loss and malnutrition are common side effects of disease process and treatment of head and neck cancer. The use of PEG tubes to aid nutrition has been shown to be effective in previous studies and suggest patients benefit from PEGs. Aim: 1) To determine the rate of insertion and use of PEGs 2) To determine complication rates Method: This study assessed 175 patients who had PEG tubes inserted from 2012 to 2016. Data was collected and extracted from patient dietitian record and analysed using SPSS. Results: 175 patients had PEGs placed from January 2012 t o December 2016. 39% of PEGs were inserted prophylactically. 67% of patients in the cohort had a diagnosis of oropharyngeal cancer. 27% of patients had laryngeal cancer. 3% had salivary gland cancer. Of all patients who received PEGs from 2012-2016, 25% gained weight and 6% of patients' weight remained stable. 68% did not experience any complication (n=119). 5% experienced a major complication of PEG infection (n=9), while the remaining 11.5% had minor complications of PEG leakage 7.5% and granuloma formation (4%). Conclusions: Weight loss is almost ubiquitous in head and neck cancers. This study demonstrated that PEGs are a useful aid for patients undergoing treatment for cancer allowing 31% of patients to gain and/or maintain weight. PEGs had relatively low rates of complications with only 5% of patients experiencing a serious complication. This study highlights that patients may benefit from PEG placement during treatment and benefits may outweigh risks.